Utility of Preoperative Electrodiagnosis Together with Peripheral Nerve High-Resolution Ultrasound: A Complex Case Report of Neurofibromatosis Type I - Basaldella, Federica; Rasera, Andrea; Zanette, Giampietro; Moscolo, Fabio; Sala, Francesco; Bonetti, Bruno; Squintani, Giovanna (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Our case report underscores the importance of electroneuromyography (ENMG) combined with peripheral nerve high-resolution ultrasound (HRUS) in the evaluation of neurofibromatosis type 1 (NF1). A 49-year-old woman affected by NF1 came to our attention because of new-onset left arm weakness and atrophy. Debulking of a cervicothoracic C7–T1 neurofibroma had been performed 8 years earlier. On current admission, magnetic resonance imaging disclosed increased lesion volume that was thought to cause the neurologic deficits by compressing the C8 root. Findings from intraoperative neurophysiologic monitoring during repeat debulking suggested that C8 root integrity had been compromised during the first operation and that the new-onset symptoms probably stemmed from peripheral nervous system damage distal to the cervical roots. Postoperative ENMG showed chronic denervation signs in the muscles innervated by C7–C8–T1 roots, moderate carpal tunnel syndrome (CTS), and ulnar nerve conduction block at the elbow. HRUS confirmed the CTS and revealed multiple neurofibromas involving the distal tract of the radial, ulnar, and median nerves. Surgical debulking was considered unnecessary in this case. ENMG combined with nerve and plexus HRUS evaluation may help identify the cause of neurologic deficits and choose the best surgical option in such complex clinical conditions as NF1.
Keywords: NF1; nerve HRUS; neurofibroma; ENMG together with nerve imaging; case report